Typhliasina Whitley 1951, an unneeded replacement name for Typhlias Hubbs 1938 (Ophidiiformes: Dinematichthyidae) - Scharpf, Christopher (Zootaxa, 2017)
Hubbs (1938) described Typhlias pearsei, representing both a new genus and species of blind cusk-eel (Ophidiiformes: Dinematichthyidae) from freshwater caves and sinkholes of the Yucatán peninsula of Mexico. Whitley (1951:67) proposed Typhliasina as a replacement name for Typhlias, citing a list of zoological names published by Neave (1950:284), but did not mention the taxon and author to which the putative senior homonym belonged. Cohen and Nielsen (1978:60) treated Typhliasina as a junior synonym of Ogilbia Jordan & Evermann 1898 in their provisional classification of the Ophidiiformes, wherein they mentioned that Typhlias Hubbs 1938 is preoccupied by Typhlias Bryce 1910 in rotifers. Typhlias Bryce 1910 has subsequently been given as the senior homonym in three important works: the FAO species catalog of ophidiiform fishes (Nielsen & Cohen 1999:134), Checklist of the Freshwater Fishes of South and Central America (Nielsen 2003:507), and a revisionary study (Møller et al. 2004:186) in which Typhliasina is resurrected from the synonymy of Ogilbia. However, a careful reading of Neave (1950) and Bryce (1910) reveals a fact that had apparently been overlooked: Typhlias Bryce 1910 is not an available name, but a lapsus for Typhlina Ehrenberg 1831.